Differences in Perceptions of the Quality of Education and Employment Effectiveness of Schools in a Non-Skills-Focused Education System - Laurisz, Norbert; Sanak-Kosmowska, Katarzyna (Journal of Public Governance, 2022)
Objectives: This paper is an attempt to identify differences between schools within the same education system in terms of how to improve students' chances of success in the labour market. The main objective is to identify differences between schools and between students' attitudes and views. In doing so, the authors take the first step in analysing the quality of education in a non-skills-focused education system.Research Design & Methods: The research was conducted in 2022 in 3 different schools in the Małopolska region. Pupils in the final classes of primary schools were surveyed. The questionnaire was completed by all students in the class (sample size: 156). The results of a survey conducted in 3 types of schools - urban public school, urban private school, and rural school - are presented.Findings: The results of the research show that there are clear differences in opinions about the quality of the education system in schools, and differences in statements about training for future development, actual involvement in training, or perceptions of entrepreneurship or attitudes towards money. The school for which these factors develop differently than for the other schools is the private school. Pupils there rate the quality of education and its employability much higher than in public schools. Pupils in private schools are much less likely to seek opportunities to acquire skills outside the education system. The analyses show that the differences between a rural public school and an urban private school are greater than those between an urban public school and a rural public school.Implications/Recommendations: The article diagnoses and shows that despite operating within an education system, one school is able to operate more efficiently and in a more employment-friendly way than others. The article suggests that a key aspect of finding solutions to the poor evaluation of the quality of education in the case of public schools is to answer the question of what characteristics of a private school influence its better perception by students. For example, it could be that private schools are more likely to encourage students to think about their future careers, that teachers provide more career-related content as part of the educational process, or that the school is generally rated significantly better than others in preparing students for working life.Contribution/Value Added: The article provides evidence that different organisations can influence the quality of the educational process, particularly in the context of students' transition to the labour market and future employment.